Аналіз загрози розпізнавання натискань клавіш фізичної клавіатури на основі даних з акселерометра смартфону - Звягіна, І. Д. (ХНУРЕ, 2025)
This study explores the threat of keystroke recognition attacks based on smartphone accelerometer data. An analysis of the experiment results is con ducted to analyze the impact of different factors on the success rate of the attack. The findings provide insights into potential security risks and highlight the feasibility of exploiting motion sensors for unauthorized data interception.
Keywords: акселерометр смартфону; смартфону